Smallpox vaccination in Nias Island, Indonesia, 1854-1915 - Junaidi (Medicina Historica, 2023)
Nias Island, during the Dutch colonial period, became one of the strategic areas because it was in the commercial route of the maritime area of the west coast of Sumatra, which directly contributed to the contact between its inhabitants and the outside world. That it was common for contact with the outside world opened up opportunities to spread several types of infectious diseases, such as smallpox. Smallpox had caused fatal damage and fear in the local population due to the high death rate and the threat of economic devastation to the population. Therefore, the Dutch colonial government attempted to overcome smallpox in Nias Island by introducing a vaccination program. This article aims to investigate the extent of the intervention of the Dutch colonial state in carrying out measures to eradicate smallpox in Nias Island.